Teachers' Efforts in Classroom Management at MIS Mardliyatul Medan School - Rahmawaty, Sakinah; Lubis, M. Anwar Azhari; Tanjung, Marisha Rahmani; Abelia, Abelia; Amirul, Bani (Lembaga Yasin AlSys, 2024)
Activities in the learning process in the classroom still seem monotonous and less interesting due to the teacher's lack of proficiency in classroom management, seen when learning students tend not to be enthusiastic in the learning process. This study aims to examine in depth the efforts made by teachers in classroom management at school. This research uses field research by taking a qualitative descriptive approach. This research was conducted at MIS Mardliyatul Medan, the data was obtained through observations to the school, interviews with teachers and documentation. In addition, researchers also obtained data through literature studies referring to journal references, books, and the internet that are in line with the findings of researchers. Based on the research results obtained at MIS Mardliyatul Medan, there are several efforts that teachers make in classroom management: teachers adjust the seating arrangement, invite students to work together, organize methods and media in the learning process and so on. Classroom management creates a comfortable and conducive classroom atmosphere, in order to create effective learning.